Human umbilical cord mesenchymal stem cells derived extracellular vesicles alleviate salpingitis by promoting M1–to–M2 transformation - Zhang, Changlin; Liao, Wei; Li, Weizhao; Li, Mengxiong; Xu, Xiaoyu; Sun, Haohui; Xue, Yaohua; Liu, Lixiang; Qiu, Jiehong; Zhang, Chi; Zhang, Xunzhi; Ye, Juntong; et al. (Frontiers in Physiology, 2023)
Background: With an increasing number of patients experiencing infertility due to chronic salpingitis after Chlamydia trachomatis (CT) infection, there is an unmet need for tissue repair or regeneration therapies. Treatment with human umbilical cord mesenchymal stem cell-derived extracellular vesicles (hucMSC-EV) provides an attractive cell-free therapeutic approach. Methods: In this study, we investigated the alleviating effect of hucMSC-EV on tubal inflammatory infertility caused by CT using in vivo animal experiments. Furthermore, we examined the effect of hucMSC-EV on inducing macrophage polarization to explore the molecular mechanism. Results: Our results showed that tubal inflammatory infertility caused by Chlamydia infection was significantly alleviated in the hucMSC-EV treatment group compared with the control group. Further mechanistic experiments showed that the application of hucMSC-EV induced macrophage polarization from the M1 to the M2 type via the NF-κB signaling pathway, improved the local inflammatory microenvironment of fallopian tubes and inhibited tube inflammation. Conclusions: We conclude that this approach represents a promising cell-free avenue to ameliorate infertility due to chronic salpingitis.